Determinants Influencing Behavioural Intention To Use Smart Mobile Travel Apps (Smta) Among Generations X, Y And Z - Sia, Yueng Hee (2023)
The evolution of smart devices and artificial intelligence technology has shifted mobile travel apps towards smart technologies. Given the high penetration rate of smartphone use but low usage and high uninstall rate of Smart Mobile Travel Apps (SMTA); limited understanding of determinants influencing the adoption of SMTA; privacy concerns and the risk of privacy information disclosure have threatened the SMTA adoption; different generations may influence behavioural intention to use SMTA. This study proposes the use of Consumer Acceptance and Use of Information Technology (UTAUT2) by including new contextual components such as Personal Innovativeness and Privacy Information Disclosure to examine the determinants influencing behavioural intention to use SMTA.